Processing of Zn-3Mg alloy by equal channel angular pressing for biodegradable metal implants - Dambatta, M.; Izman, S.; Kurniawan, Denni; Hermawan, H. (King Saud University Press - King Saud University, 2017)
Zn-based alloys have been studied as new biodegradable metals owing to its slower corrosion rate compared to Mg-based alloys and its high potential for mechanical properties improvement. The present work attempts to improve mainly the mechanical properties of a eutectic Zn-3Mg alloy via equal channels angular pressing (ECAP). Cast Zn-3Mg alloy was homogenized at 370 °C for 15 h and quenched in water before subjected to 2 steps ECAP process. Results showed that the process decreases the alloy's grain size from 48 µm in the as cast to 1.8 µm after 2-passes of ECAP. A remarkably increase of yield strength, tensile strength and elongation was achieved from 65 MPa, 84 MPa and 1.3% (as cast) to 205 MPa, 220 MPa and 6.3% (2-ECAP), respectively. Corrosion rate of the alloy was fairly altered from 0.30 mm/year (as cast) to 0.24 mm/year (2-ECAP). The combination of homogenization and ECAP is therefore viewed as a potential process to improve mechanical properties of Zn-Mg alloys.